Methods Of Overcoming The Difficulties Of Teaching Professional Texts In English - Soliyev Umidjon Yulchivoevich (Academia One, 2024)
his article is devoted to the method of overcoming difficulties in teaching students to read professional texts in English, in which higher education institutions teach professional texts in English classes for non-philology students. The description of the methodical problem of teaching professional texts is widely covered. It has been suggested that teaching the language based on professional texts in English classes is a more effective method, but the development of reading competence in professional English teaching has not been thoroughly studied. The article presents the scientific researches and the obtained results on the use of English texts in the teaching of the English language in a professional manner. This article is important for foreign language teachers in the process of language teaching, and for students studying foreign languages in the preparation of graduation papers.
Keywords: English language; summary text; additional texts; exercises for teaching reading